2002
DOI: 10.1080/714000979
|View full text |Cite
|
Sign up to set email alerts
|

State Formation and Territoriality in the European Union

Abstract: This article analyses the process of the expansion and integration of the EU from the perspective of a transformation to a competitive state formation. The recent construction of the EU is based on institutional arrangements which aim to combine different politics of scale with a general improvement of economic competitiveness and administrative efficiency. Recent theoretical advancement in state theory are applied in order to emphasise innovative aspects of European integration. After a concise overview about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…without it being possible to determine with certainty what are national preparatory processes and what are EU level negotiations". Much work in political geography attests to the interrelations between territory and identity and their manipulation by geographical sites of authority (Heeg and Ossenbrugge, 2002;Paasi, 2001Paasi, , 2005Painter, 1995Painter, , 2001Painter, , 2003Rodriguez-Pose, 2002;Scott, 2002Scott, , 2005Smith, 2002;Western, 2007), which again is absent from many Europeanisation studies, suggesting a third discontent in relation to depictions of power (Table 1). For example, while current analyses have fruitfully identified the 'uploading' of political preferences to the EU level (see Howell, 2004;Radaelli, 2004), Europeanisation's frequent invocation as impact of the EU upon national political life and its consequent transformation overlooks the capacity of states for selective acquiescence in this process, enabling national political élites to steer Europeanisation in national territories on terms that buttress existing state orders (see Buller and Gamble, 2002).…”
Section: Disciplinary Perspectives On Europeanisation: Identifying Thmentioning
confidence: 94%
“…without it being possible to determine with certainty what are national preparatory processes and what are EU level negotiations". Much work in political geography attests to the interrelations between territory and identity and their manipulation by geographical sites of authority (Heeg and Ossenbrugge, 2002;Paasi, 2001Paasi, , 2005Painter, 1995Painter, , 2001Painter, , 2003Rodriguez-Pose, 2002;Scott, 2002Scott, , 2005Smith, 2002;Western, 2007), which again is absent from many Europeanisation studies, suggesting a third discontent in relation to depictions of power (Table 1). For example, while current analyses have fruitfully identified the 'uploading' of political preferences to the EU level (see Howell, 2004;Radaelli, 2004), Europeanisation's frequent invocation as impact of the EU upon national political life and its consequent transformation overlooks the capacity of states for selective acquiescence in this process, enabling national political élites to steer Europeanisation in national territories on terms that buttress existing state orders (see Buller and Gamble, 2002).…”
Section: Disciplinary Perspectives On Europeanisation: Identifying Thmentioning
confidence: 94%
“…First, research has shown how European integration has accelerated change in patterns of governance up, down and across member states, their regions and territories (Agnew 2001; Brenner et al . 2003; Heeg and Ossenbrugge 2002). Second, geographers have examined how the territorial identities of states acceding to the EU (most recently East and Central European states in 2004 and 2007) are beginning to challenge implicit West European values embedded within the integration project, with Paasi (2005, 582) commenting that eastward expansion has brought into play ‘a key territorial element in the construction of a new territorial identity’ for the EU (cf.…”
Section: Introductionmentioning
confidence: 99%
“…As Heeg and Oßenbrügge put it, European integration is about 'processes of de-nationalisation, internationalisation and destatisation of the national state' which are 'forms of crisis management in order to foster economic restructuring and at the same time to partition off deficits of legitimacy which are accompanying effects'. 66 German elite preferences for liberal markets and insistence on independent legal structures have been drawn into conflict with a desire for reconciliation and harmonious political relations with CEE. 67 The political class wants to avoid suspicion or accusation that Germany has menacing ulterior motives.…”
Section: Resultsmentioning
confidence: 99%